El Excentrico, 1954-11-05 - Garcia, Humberto:::Publisher:::::::::::: (Garcia Printing; San Jose, California, 2023)
November 5, 1954 [5 de noviembre de 1954]. Ano 5, No. 1. Cover contains a group photo with Humberto Garcia, Jr, Jerry Busch, and Keeny Janovitch, who were comparing biceps with wrestler, Jesus Ortega. The eadline reads, "310 lbs. Mat Star Gladiator."